Dual Faces of Malnutrition : Managing a Pediatric Case of Marasmus Kwashiokor in a Distric General Hospital - Yustika Amalia; Aty Firsiyanti; Yusian Eri Fitria; Lasmadu Suyanto (JurnalMU: Jurnal Medis Umum, 2026)
Marasmus kwashiorkor is a severe form of protein-energy malnutrition (PEM) combining features of both marasmus and kwashiorkor, and poses a significant threat to child health in low-resource settings. This case report aims to describe the clinical profile and management outcome of a 6-month-old infant diagnosed with marasmus-kwashiorkor at Dr. Soegiri General Hospital, Lamongan. The infant presented with chronic diarrhea, significant weight loss, generalized edema, hypoalbuminemia, and characteristic skin changes. Management was initiated following the World Health Organization (WHO) protocol for severe acute malnutrition (SAM), including cautious rehydration with ReSoMal, correction of electrolyte imbalances, antibiotics, and phased nutritional rehabilitation using F-75 and F-100 therapeutic milks. Micronutrient supplementation and infection prevention measures were also administered. The patient showed progressive clinical improvement, with resolution of edema by day ten and weight gain at 5 g/kg/day. This case highlights the critical importance of early identification and comprehensive, guideline-based treatment of SAM. Public health interventions addressing maternal education, breastfeeding practices, and food security are essential to prevent such cases and reduce child mortality in similar populations.